Pengaruh Kemanfaatan Dan Kemudahan QRIS Di Ewallet Terhadap Efisiensi Pembayaran Digital Pada Mahasiswa STAIN Mandailing Natal: Irwansyah Nasution - Irwansyah Nasution (Program Studi Perbankan Syariah Jurusan Syariah, Ekonomi dan Bisnis Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal (STAIN MADINA), 2026)
This research is motivated by the low level of utilization of QRIS as a digital payment tool among students even though it is widely available and is considered to have many advantages. The purpose of this study is to determine whether the perception of the usefulness and convenience of QRIS has a significant effect on the efficiency of digital payments among students of STAIN Mandailing Natal. The method used is a quantitative approach with multiple linear regression analysis techniques, as well as hypothesis testing through partial tests (t), simultaneous tests (F), and coefficient of determination tests (R2). The results show that the perception of the usefulness of QRIS (X1) has a significant effect on the efficiency of digital payments among students of STAIN Mandailing Natal, evidenced by the t-value of 2.175 > t-table 1.668 so that Ho is rejected and Ha is accepted. Likewise, the perception of the convenience of QRIS (X2) has a significant effect on the efficiency of digital payments with a t-value of 5.601 > t-table 1.668 so that Ho is rejected and Ha is accepted. Furthermore, the F-test results show F count of 42.674 > F table of 3.14 with a significance level of 0.000 < 0.05, thus rejecting Ho and accepting Ha. Thus, both partially and simultaneously, the usefulness and convenience of QRIS significantly influence the efficiency of digital payments. Keywords: Benefits, Convenience, Efficiency of Digital Payments